In vitro anthelmintic efficacy of Acacia nilotica pods on eggs and adult worms of Haemonchus contortus - Zabre, G; Tindano, B; Dicko, A; Bayala, B; Kaboré, A; Belem, A M G; Tamboura, H H (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Gastrointestinal nematodes are major pathologies in small ruminants. The aime of the present study was to evaluate the in vitro anthelmintic effect of aqueous and acetone extracts of pods of Acacia nilotica on the eggs and adult worms of Haemonchus contortus. Eggs and worms were exposed to five increasing concentrations (1.25; 2.5; 5; 10 and 20 mg/mL). The results showed dose-dependent ovicidal (P<0.001) and vermicide (P<0.05) activity against H. contortus. For the egg hatch inhibition assay (EHA), the rate of inhibition were ranging from 31 to 70% for aqueous extracts and from 41 to 81% for acetone extract. Benzal have obtained the highest inhibition rate of 91%. For adult nematode mortality test (AMT), no mortality was recorded between 0h and 2h in all group treated as well as the two controls. Mortalities were recorded from the 4th and 6th hour of incubation. Concentrations of 10 and 20 mg/mL recorded the highest mortality rates (>80%) after 4 h of incubation. These results suggest that A. nilotica pods can be used in the control of gastrointestinal nematodes.